Effect of Team Games Tournament Model with Big Book Media on Students’ Collaboration Skills in Local Dance Learning - Paraswati, Lintang; Hairunnis, Mirham Nurul; Saputra, Ayub Qadha (Journal of Educational Sciences, 2025)
21st-century education demands that children learn to work together from an early age, but arts and culture education in elementary schools is still largely traditional and teacher-centered, which limits opportunities for collaboration. This study aims to investigate how students' collaborative skills in traditional dance education are affected by the Team Games Tournament (TGT) model that uses Big Book media. Twenty fourth-grade students from SDN 39 in Bima City were chosen through a saturated sampling process as part of the study's quasi-experimental design, which used a one-group pretest-posttest approach. A collaboration ability assessment, observational sheets, and documentation were among the research tools. Normality tests and Paired Sample t-Tests were used for data analysis. The results showed that using TGT in conjunction with Big Book improved students' group collaboration, communication, accountability, and engagement. Big Book media enhanced student participation in educational competitions and improved understanding of traditional dance content. According to this study, the combination of TGT and Big Book greatly improved students' teamwork skills and made it easier to implement the Pancasila Student Profile within the Independent Curriculum.